Ranking Dairy Sires Using Genetic Selection Indices Based on Financial Investment Methods versus Lifetime Net Merit: Description and Spreadsheet - Michael Schmitt; Albert De Vries (EDIS)
This factsheet describes ways to rank dairy sires using genetic selection indices based on financial investment methods versus Lifetime Net Merit. The factsheet also discusses a spreadsheet that contains the calculations. Written by Michael Schmitt and Albert De Vries, and published by the UF/IFAS Department of Animal Sciences, May 2021.